Analisis Nilai Pancasila Pada Perkembangan Teknologi Digital Untuk Mendorong Pertumbuhan Ekonomi - Fatima Sadira; Malfa Liya; Maria Marselina; Marisa Yanti; Scerly Faula; Shalli Layla; Sri Miftahuljannah; Ilham Hudi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The development of the digital economy is one of the most important strategies to transform the Indonesian economy. In the era of globalization, economic improvement has become increasingly important to improve the general welfare. However, efforts to improve the economy must be equitable and prioritize the interests of all of us. The right and fast way to measure the compatibility between economic ideals / goals with the Indonesian state is through Pancasila. The purpose of this study is to analyze the values of Pancasila in the development of the digital economy. This research uses the library research method by examining a number journals. The results of this study show that the application of Pancasila values in the development of the digital economy is very important to create human welfare.